Exceeding (low) expectations Autonomy, bureaucratic integrity, and capacity in the 2010 elections. [article]. - Calimbahin, Cleo.
Building quality democracy takes time. It requires a constant review of the performance of institutions that are tasked to deliver in concrete ways the democratic ideal. Improving democratic institutions requires sustained reform efforts. Election administration and election commissions need to be examined against this backdrop of broader democratization issues. Given the importance of election administration in the study of democratic processes, there are very few studies that focus on election administration. By focusing on a specific institution tasked to replicate the ideals of democracy such as the COMELEC, this study offers insights into a deeper understanding of autonomy, bureaucratic integrity and capacity. Though mostly overlooked, election administration plays a vital role in the study of broader democratization questions. Elections promise continuity and stability. But if election administration is done poorly due to the lack of autonomy, integrity, and capacity then it becomes an unsettling and destabilizing exercise. -- (from the author)
Keywords: Political Science-Periodicals.; Elections; Democratization; Election administration; COMELEC; Political institution; State capacity; Corruption; Clientelism; Bureaucratic reform